A wireless transmission coupling structure with low electromagnetic force disturbance and stable coupling coefficient. Issue 1 (February 2021) - Xing, Zikang; Yan, Kui; Han, Gao; Li, Xiaoping; Liu, Yanming
Abstract: In the inductive wireless power transmission, electromagnetic force, which between the primary part and the secondary part, may cause the non-contact free motion and cause bad side effects on transmission. In order to calculate the force, magnetic vector potentials differential equations, based on linear array, are built, and the expression of the electromagnetic force is produced by solving this equation system.